Phenomenal consciousness and cognitive access - Overgaard, Morten (Philos Trans R Soc Lond B Biol Sci, 2018)
In consciousness research, it is common to distinguish between phenomenal consciousness and access consciousness. Recently, a number of scientists have attempted to show that phenomenal content can be empirically separated from cognitive access and, accordingly, that the mental content that is accessed is not (always) identical to the content that is experienced. One notable position is that of Ned Block who suggests that phenomenal content overflows cognitive access. I will review the evidence and show that existing data, in fact, do not demonstrate overflow. I will further argue that overflow is theoretically possible—yet highly difficult to empirically demonstrate—under the condition that ‘cognitive access’ is defined as working memory or attention. However, if ‘access’ is defined as information becoming ‘cognitively available’, in a broader sense, I will argue that a separation between subjective experience and access is impossible. This article is part of the theme issue ‘Perceptual consciousness and cognitive access’.